2020
DOI: 10.1084/jem.20201011
|View full text |Cite
|
Sign up to set email alerts
|

The T cell CD6 receptor operates a multitask signalosome with opposite functions in T cell activation

Abstract: To determine the respective contribution of the LAT transmembrane adaptor and CD5 and CD6 transmembrane receptors to early TCR signal propagation, diversification, and termination, we describe a CRISPR/Cas9–based platform that uses primary mouse T cells and permits establishment of the composition of their LAT, CD5, and CD6 signalosomes in only 4 mo using quantitative mass spectrometry. We confirmed that positive and negative functions can be solely assigned to the LAT and CD5 signalosomes, respectively. In co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
68
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 41 publications
(79 citation statements)
references
References 75 publications
2
68
0
Order By: Relevance
“…Upon CD5 and CD6 receptor ligation and phosphorylation, several downstream intracellular signal transducers are engaged. The multiple interactors recruited to the CD5 signalosome (SHP-1, Ras-GAP, Cbl-b, UBASH3A, ANKRD13A and CK2) finally end up down-modulating lymphocyte activation [ 42 , 43 , 44 , 45 , 46 ]. As for the CD6 signalosome, the reported interactors (SLP-76, ZAP-70, VAV1, GRB2, GRAP2, GRK, GADS, TSAd, UBASH3A, SHIP1, ARHGAP45 and Syntenin) end up providing co-inhibitory or co-stimulatory functions [ 46 , 47 , 48 , 49 , 50 ].…”
Section: The Case Of Lymphocyte Scavenger Receptors Cd5 mentioning
confidence: 99%
“…Upon CD5 and CD6 receptor ligation and phosphorylation, several downstream intracellular signal transducers are engaged. The multiple interactors recruited to the CD5 signalosome (SHP-1, Ras-GAP, Cbl-b, UBASH3A, ANKRD13A and CK2) finally end up down-modulating lymphocyte activation [ 42 , 43 , 44 , 45 , 46 ]. As for the CD6 signalosome, the reported interactors (SLP-76, ZAP-70, VAV1, GRB2, GRAP2, GRK, GADS, TSAd, UBASH3A, SHIP1, ARHGAP45 and Syntenin) end up providing co-inhibitory or co-stimulatory functions [ 46 , 47 , 48 , 49 , 50 ].…”
Section: The Case Of Lymphocyte Scavenger Receptors Cd5 mentioning
confidence: 99%
“…T cells express more than 20 GAPs, and the function and mechanism of action of most of them remain to be elucidated (Stein & Ruef, 2019). We recently identified the ARHGAP45 GAP among the signaling protein complexes that assemble in mouse primary T cells (Voisinne et al , 2019; Mori et al , 2021). ARHGAP45, also known as HMHA1 (human minor histocompatibility antigen 1), has been first described in human and comprises an N‐terminal BAR domain followed by a C1 and a RHO GAP domain (de Kreuk et al , 2013).…”
Section: Introductionmentioning
confidence: 99%
“…A recent proteomic study revealed that the LAT signalosome exhibits dynamic time-dependent interaction relationships with the transmembrane receptors CD5-and CD6-assembled signalosomes (81). According to that study, the LAT signalosome mostly plays a dominant role as an activating signaling pathway node, as characterized by its ability to activate SOS-ERK and PLCg1-NFAT pathways (81). However, unlike the LAT signalosome, the CD5 signalosome is enriched with many proteins with inhibitory functions, including Cbl-b and Ubash3A (81).…”
Section: Lat Signalosome Maintains a Dynamic Interactome With The Cd5mentioning
confidence: 99%
“…According to that study, the LAT signalosome mostly plays a dominant role as an activating signaling pathway node, as characterized by its ability to activate SOS-ERK and PLCg1-NFAT pathways (81). However, unlike the LAT signalosome, the CD5 signalosome is enriched with many proteins with inhibitory functions, including Cbl-b and Ubash3A (81). Interestingly, the CD6-induced signalosome functions as a buffering zone, competing interacting proteins with either the inhibitory CD5 signalosome or with the stimulatory LAT signalosome.…”
Section: Lat Signalosome Maintains a Dynamic Interactome With The Cd5mentioning
confidence: 99%
See 1 more Smart Citation